Human factors in the justification of an advanced manufacturing system - Dahlen, Per; Bolmsjo, Gunnar S.
The purpose of this article is to analyze the impact of human factors on the design of an Advanced Manufacturing System (AMS).
Keywords: Advanced manufacturing system (AMS).; Robotics; Life cycle cost (LCC) analysis